2018
DOI: 10.1038/s41467-018-07430-4
|View full text |Cite
|
Sign up to set email alerts
|

A single Gal4-like transcription factor activates the Crabtree effect in Komagataella phaffii

Abstract: The Crabtree phenotype defines whether a yeast can perform simultaneous respiration and fermentation under aerobic conditions at high growth rates. It provides Crabtree positive yeasts an evolutionary advantage of consuming glucose faster and producing ethanol to outcompete other microorganisms in sugar rich environments. While a number of genetic events are associated with the emergence of the Crabtree effect, its evolution remains unresolved. Here we show that overexpression of a single Gal4-like transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…A PYK‐induced change in glycolytic flux is hence the cause, not a consequence, of major changes in cellular metabolism, regulation and physiology. The finding that a new metabolic programme can be triggered by an intracellular cue is consistent with a report showing that overexpression of one transcription factor in Komagataella phaffii is sufficient to turn this Crabtree‐negative yeast into a Crabtree‐positive one (Ata et al , ). These findings support the idea that a flux‐sensing mechanism could regulate the balance between respiration and fermentation (Huberts et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…A PYK‐induced change in glycolytic flux is hence the cause, not a consequence, of major changes in cellular metabolism, regulation and physiology. The finding that a new metabolic programme can be triggered by an intracellular cue is consistent with a report showing that overexpression of one transcription factor in Komagataella phaffii is sufficient to turn this Crabtree‐negative yeast into a Crabtree‐positive one (Ata et al , ). These findings support the idea that a flux‐sensing mechanism could regulate the balance between respiration and fermentation (Huberts et al , ).…”
Section: Discussionsupporting
confidence: 89%
“…- However, other high-throughput technology methods such those using microarrays, based qualitative fluorescent detection, and/or RNA sequencing (RNAseq), which quantify the number of transcripts present in a sample by whole transcriptome sequencing, have arisen as helpful workhorses. In fact, these methods provide a robust overview of all transcripts (Baumann et al, 2010 ; Ata et al, 2018 ) and are thus especially useful when increased gene coverage is needed.…”
Section: Continuous Cultivation Provides An Excellent Tool For Systemmentioning
confidence: 99%
“…It is worth mentioning that Crabtree effect corresponds to the respiro-fermentative phenotype widely reported for S. cerevisiae , however a similar phenomenon has been observed also in cancer cells (Warburg effect). In order to generate an alternative model for Warburg effect studies, Ata et al ( 2018 ) convert Crabtree negative P. pastoris into a Crabtree positive. While determination of Crabtree phenotype was achieved using short- and long-term studies in chemostat cultures, RNASeq transcriptome and 13 C central metabolism flux analysis were performed in batch cultures.…”
Section: Continuous Cultivation Provides An Excellent Tool For Systemmentioning
confidence: 99%
“…However, the results of the previous studies indicated that P. pastoris produced a small amount of ethanol as a byproduct during the fermentation under aerobic conditions and could also utilize ethanol as a sole carbon source (Inan & Meagher, ). It has recently been demonstrated that the overexpression of a single gene is sufficient to trigger Crabtree phenotype leading to the production of ethanol under aerobic conditions in P. pastoris (Ata et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As put forward by several studies, in P. pastoris , only under hypoxic conditions fermentation pathway is switch on and ethanol is produced (Crab‐tree negative phenotype; Baumann et al, , ). Recently, it has been also shown that by overexpression of only a single transcription factor ( CRA1 ), glycolytic flux is increased and ethanol is produced even under aerobic conditions leading to the Crabtree positive phenotype (Ata et al, ). This underlines just how deletion or overexpression of a gene causes significant changes in the glucose consumption characteristics of the cells.…”
Section: Discussionmentioning
confidence: 99%